A Highly Permeable Aligned Montmorillonite Mixed‐Matrix Membrane for CO2 Separation. (17th June 2016) - Qiao, Zhihua; Zhao, Song; Wang, Jixiao; Wang, Shichang; Wang, Zhi; Guiver, Michael D.
Abstract: Highly permeable montmorillonite layers bonded and aligned with the chain stretching orientation of polyvinylamineacid are immobilized onto a porous polysulfone substrate to fabricate aligned montmorillonite/polysulfone mixed‐matrix membranes for CO2 separation. High‐speed gas‐transport channels are formed by the aligned interlayer gaps of the modified montmorillonite, through which CO2 transport primarily occurs. High CO2 permeance of about 800 GPU is achieved combined with a high mixed‐gas selectivity for CO2 that is stable over a period of 600 h and independent of the water content in the feed.